Rim esponja medular, litíase, hipercalciúria e hiperuricosúria em criança. Relato de um caso e evolução - Macedo, C. S. [UNESP]; Riyuzo, M. C.; Bastos, H. D.; Morcelli, J. (Jornal De Pediatria, 1996)
The medullary sponge kidney is rare in children and may present it self with hematuria and nephrolithiasis. We report a case of medullary sponge kidney in a child with nephrolithiasis, hypercalciuria, hyperuricosuria and prolonged treatment which avoided the recurrence of nephrolithiasis.
Medullary sponge kidney, nephrolithiasis, hypercalciuria and hyperuricosuria in a child. Report of a case and follow-up